PENGARUH KEDISIPLINAN TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPA KELAS IV DI SD ISLAM NU PUNGKURAN - Retna Widyasari; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
RETNA WIDYA, Effect of Discipline on Student Learning Outcomes ofScience Class IV Subjects in Nu Pungkuran Islamic Elementary SchoolLearning achievement is a measure of student ability after doing study activitiesover a period of time. Learning achievement influenced by several factors, oneunya that is learning discipline. Difference discipline learning on each studentraises a learning achievement different as well as disipl in and grade 4 learningachievements tails SD Islam NU Pungkuran Based on this background, thisstudy aims for knowing:(1) the level of student learning discipline, (2) the level of student achievement,(3) the influence of learning discipline on student achievement, and (4) how bigpinfluence the discipline of learning on student achievement.Research this using the method descriptive survey with approach quantitative Population in the study that is all class students IV SD Islam NU Pungkuranamounted to six students. Research semany sixStudents which is determined use technique Proportional Random Sampling.Research variable covering the discipline of learning as the independentvariable and learning achievement as variable terikat. Data collectiontechniques use questionnaires, observations and documentation. Theprerequisite analysis test shows that the data is normally distributed and linearso tecology hypothesis testing using anali sis regresi linear simple.The results of the study me show that: (1) the level of student learningdiscipline amounted to 75.55% and included in the category strong, (2) level oflearning achievement students amounted to 78.38 and included in eithercategory, (3) Value sig amount 0,000. Therefore 0.000 <0.05, then Ho rejectedand Ha accepted meaning there is a significant influence of learning disciplineon student achievement, (4) coefficient of determination (R2) 0.567 indicates thepercentage of donations the influence of independent variable equal to 56,7%.This shows that 56.7% student achievement is influenced by learning discipline,while 43.3% influenced by other factors not discussed in the study. Started onthe results of research, then all parties both teachers and parents should bepayattention and mening katkan discipline of learning students so it can achievemore optimal learning achievement.Keywords: Discipline Blearn Learning achievement